SHARIA GOVERNANCE IN ISLAMIC FINANCIAL INSTITUTIONS: A COMPARATIVE REVIEW OF MALAYSIA AND INDONESIA - Faizi, Faizi; Bin Shuib, Mohd Sollehudin (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
As important participants in Sharia governance, Malaysia and Indonesia emphasize the importance of a Sharia supervisory board at the institutional level to ensure compliance with Islamic principles. This study provides a comparative analysis of Sharia governance practices in Indonesia and Malaysia, focusing on the key differences and similarities between the Sharia governance frameworks in Malaysia and Indonesia. The method adopted in this study was document research. This method allows researchers to access a wide range of information and perspectives from various sources such as books, academic journals, government reports, and online databases. The findings reveal that both Malaysia and Indonesia have implemented Sharia governance frameworks in their Islamic financial institutions. However, their structures and regulatory frameworks differ from each other. Malaysia follows a two-tier structure with a comprehensive framework, whereas Indonesia follows a decentralized model with dispersed regulations. Both countries require the establishment of a Sharia committee at the institutional level to ensure compliance with the Sharia principles. Therefore, this comparative analysis enhances the understanding of Sharia governance in Islamic banking and finance, shedding light on the strengths and weaknesses of Malaysia and Indonesia's frameworks